Programming to Learn in Primary Schools: Including Scratch Activities in the Curriculum - Chioccariello, Augusto; Freina, Laura (European conference on games based learning, 2019)
The Italian Ministry of Education is promoting the introduction of coding and computational thinking in compulsory school. While it is still unclear how the Ministry will reform the current curriculum guidelines to introduce computing, Italian schools have anyway reached a record level of participation in events like the EU Code Week and the Hour of Code. "Programming to Learn in Primary School" is a project we are conducting following Papert's claim that "children can learn to program and that learning to program can affect the way they learn everything else". The project is in its second year and involves all primary school grades, from 1 to 5. The children in grade 1 and 2 work with programmable play kits with tangible interfaces. From grades 3 to 5 the online Scratch programming environment is used. To become proficient in a new language (the programming language here), children need time to learn how to use it expressively and become part of a social context where the language is practised. So the Scratch online community is a perfect match. Children love sharing their work and remixing, as well as the social features of Scratch for adding likes and commenting on each other's projects. All the grade 3 to 5 children in the project attend a weekly computer lab class, playing with Scratch. In grades 4 and 5, they work on individual projects during the first half of the school year; in the second half, they work in small groups on a common theme that the teacher selects from those studied in class (the European Parliament, hydro-geological risk, etc.). The project aim is to develop and validate a vertical curriculum for the introduction of programming in primary schools as an expressive new language. In the lower grades the focus is on becoming fluent with the programming language, while integration with curricular disciplines is sought in the last two years.